An international comparison of male and female breast cancer incidence rates 1. Issue 8 (12th October 2012) - Ly, Diana; Forman, David; Ferlay, Jacques; Brinton, Louise A.; Cook, Michael B.
Abstract Global international trends in female breast cancer incidence have been described previously but no comparable analysis of male breast cancer incidence rates has been conducted. We obtained male and female case and population data using Cancer Incidence in Five Continents (CI5). We calculated age‐adjusted, sex‐specific incidence rates and female‐to‐male incidence rate ratios (FMIRRs) and compared trends of such for the period 1988–2002. This analysis included 8, 681 male breast cancer cases and 1.14 million female breast cancer cases. The highest male incidence rate was observed in Israel at 1.24 per 100, 000 man‐years, and the highest female incidence rate was observed in the United States at 90.7 per 100, 000 woman‐years. The lowest incidence rates for males (0.16) and females (18.0) were observed in Thailand. In general, male breast cancer incidence trends were variable; a minority of countries displayed evidence for an increase. In contrast, female incidence rates have been increasing in a majority of countries. The Pearson correlation coefficient (r) for male and female breast cancer incidence rates by country during 1988–2002 was 0.69. Male breast cancer rates were generally less than 1 per 100, 000 man‐years, in contrast to the much higher rates of female breast cancer, providing for an overall FMIRR of 122. The differences in both incidence rates and time trends between males and females may reflect sex differences in underlying risk factors, pathogenesis, and/or overdiagnosis. Conversely, the high correlation between male and female breast cancer incidences may indicate that both sexes share some common risk factors for breast cancer.